A Study on BCG Vaccination Using Bifurcated Needle in Babies - Gunardi A.S.; Suyaka Suyaka; L. Ratna Budiarso (Indonesian Pediatric Society, 1979)
Investigation was done on 527 babies comparing BCG vaccination by bifurcated needle and intradermal method. For this study Japanese and Biofarma BCG vaccines were used.